The Effect of CSR, Brand Attitude, and Perceived Value on Purchase Intention at Uniqlo - Vicky Alvian; Anak Agung Ketut Diatmika (Universitas Dr. Soetomo, 2024)
The number of fast fashion companies in Indonesia makes competition very tight in a business, this emphasizes the role of corporate social responsibility carried out by company owners with the aim of sustainable promotion to obtain brand attitude, perceived value, and purchase intention. Corporate social responsibility that is well received is a contributing factor in creating a brand attitude which also influences the perceived value and purchase intention. The purpose of this study is to analyze the effect of corporate social responsibility, brand attitude, and perceived value on purchase intention. This research was conducted in Jakarta with a descriptive causality research design with a quantitative method approach and using purposive sampling techniques. Data was collected from 231 respondents who had visited the Uniqlo store. The conceptual model was analyzed using Structural Equation Modeling. The research findings reveal that corporate social responsibility can improve brand attitude. Then, brand attitude can increase perceived value and purchase intention. Furthermore, perceived value can increase purchase intention. The contribution of this research can provide insight to fast fashion company owners to develop businesses and can plan and implement marketing strategies so that brand attitudes and good judgment are formed by consumers to create purchase intentions on Uniqlo products.